1981
DOI: 10.1161/01.hyp.3.5.622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostaglandin inhibition on the hypertensive action of sodium-retaining steroids.

Abstract: SUMMARY To compare the sodium-retaining action and the effect on blood pressure (BP) of certain steroids, nine nonnotensive subjects were given fludrocortisone 0.3 rag orally twice a day (b.i.d.), five received deoxycorticosterone acetate (DOCA) 10 rag IM b.i.d., and this was compared to the effect of fludrocortisone or DOCA plus prostaglandin inhibition (PI) or PI given alone. PI was accomplished with either indomethacin 50 mg or ibuprofen 400 mg every 6 hours. All patients received 250 mEq Na + daily. Fludro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…218 -221 NSAIDs may also contribute to increased vascular resistance due to increased ET-1 synthesis and/or altered arachidonic metabolism. [222][223][224][225][226] They also interfere with BP control in the elderly through partial reversal of antihypertensive effects of diuretics, 218,[227][228][229][230] beta-receptor antagonists, and ACEIs [231][232][233] and ARBs, but not CAs. NSAIDs antagonize antihypertensive effects of beta blockers more than vasodilators or diuretics.…”
Section: Alcohol Several Mechanisms Have Been Suggestedmentioning
confidence: 99%
“…218 -221 NSAIDs may also contribute to increased vascular resistance due to increased ET-1 synthesis and/or altered arachidonic metabolism. [222][223][224][225][226] They also interfere with BP control in the elderly through partial reversal of antihypertensive effects of diuretics, 218,[227][228][229][230] beta-receptor antagonists, and ACEIs [231][232][233] and ARBs, but not CAs. NSAIDs antagonize antihypertensive effects of beta blockers more than vasodilators or diuretics.…”
Section: Alcohol Several Mechanisms Have Been Suggestedmentioning
confidence: 99%
“…NSAIDs may also contribute to increased vascular resistance due to increased ET-1 synthesis and/or altered arachidonic metabolism (222)(223)(224)(225)(226). They also interfere with BP control in the elderly through partial reversal of antihypertensive effects of diuretics (218,(227)(228)(229)(230), beta-receptor antagonists, and ACEIs (231-233) and ARBs, but not CAs.…”
Section: Thyroid Status and Hypertensionmentioning
confidence: 99%
“…As far as PGI2 and blood pressure control is concerned, it has been demonstrated that PGI2 modulates vascular reactivity and blood pressure by different pathophysiological mechanisms [5]. PGI2 systhesis occurs in capillary endothelium and its inhibition by indomethacin administration enhances vascular responsiveness to vasoconstrictors, raising arterial blood pressure [18][19][20]. Furthermore, rats predisposed to salt-induced hypertension exhibit impaired generation of vascular PGIz compared with appropriate control animals [21].…”
Section: Discussionmentioning
confidence: 99%